The neural mechanisms underlying the aging-related enhancement of positive affects: electrophysiological evidences - Meng, Xianxin; Yang, Jiemin; Cai, AYan; Ding, XinSheng; Liu, Wenwen; Li, Hong; Yuan, JiaJin (Frontiers in Aging Neuroscience, 2015)
Background: Previous studies reported that old adults, relative to young adults, showed improvement of emotional stability and increased experiences of positive affects. in order to better understand the neural underpinnings behind the aging-related enhancement of positive affects, it is necessary to investigate whether old and young adults differ in the threshold of eliciting positive or negative emotional reactions. However, no studies have examined emotional reaction differences between old and young adults by manipulating the intensity of emotional stimuli to date. To clarify this issue, the present study examined the impact of aging on the brain’s susceptibility to affective pictures of varying emotional intensities. Methods: We recorded event-related potentials for highly negative (HN), mildly negative (MN) and neutral pictures in the negative experimental block; and for highly positive (HP), mildly positive (MP) and neutral pictures in the positive experimental block, when young and old adults were required to count the number of pictures, irrespective of the emotionality of the pictures. Results: Event-related potentials (ERP) results showed that LPP (Late positive potentials) amplitudes were larger for HN and MN stimuli compared to neutral stimuli in young adults, but not in old adults. By contrast, old adults displayed larger LPP amplitudes for HP and MP relative to neutral stimuli, while these effects were absent for young adults. In addition, old adults reported more frequent perception of positive stimuli and less frequent perception of negative stimuli than young adults. The post-experiment stimulus assessment showed more positive ratings of Neutral and MP stimuli, and reduced arousal ratings of HN stimuli in old compared to young adults. Conclusions: These results suggest that old adults are more resistant to the impact of negative stimuli, while they are equipped with enhanced attentional bias for positive stimuli. The implications of these results